Problems of biology learning and evaluation analysis at the cipp model-based higher education level - Ida Bagus Ari Arjaya; Ketut Suma (Biosfer: Jurnal Pendidikan Biologi, 2023)
The purpose of this study was 1) to determine what the problems of biology learning at the college level are based on the learning domain; 2) to examine the biology learning curriculum's context; 3) Evaluate the biology learning curriculum input; 4) Evaluate the biology learning curriculum process, and 5) Evaluate the biology learning curriculum at Universitas Mahasaraswati Denpasar, Indonesia. This research includes evaluative research with a mixed methods, explanatory sequential design approach. The data retrieval technique in this study used the purposive samplingmethod namely, 57 students and 11 lecturers became research samples. The results of this study are: 1) cognitive domain issues are misconceptions, high-level thinking skills, and gender. Affective domain problems include stress, scientific attitudes, and attitudes toward science. Furthermore, the psychomotor domain problems are basic process skills and experimental processes; 2) The context of curriculum problem related to outcome based education (OBE) is still generic and has not involved the business world and industry; 3) Input evaluation results based on leadership and educational facilities are relatively good, but still development in human resources (HR) section. Furthermore, the lecturer's teaching competencies are categorized well; 4) The evaluation of the lecture process is consistently conducted by monitoring Internal Quality Audit and ISO 21001: 2018; 5) The results of the curriculum evaluation product are relatively good but still constrained regarding the fulfillment of doctoral qualifications and student publications. Each of these issues has been assigned separately for follow-up.